Nuclear import of the thyroid hormone receptor α1 is mediated by importin 7, importin β1, and adaptor importin α1. (5th January 2016) - Roggero, Vincent R.; Zhang, Jibo; Parente, Laura E.; Doshi, Yazdi; Dziedzic, Rose C.; McGregor, Emma L.; Varjabedian, Arev D.; Schad, Sara E.; Bondzi, Cornelius; Allison, Lizabeth A.
Abstract: The thyroid hormone receptor α1 (TRα1) is a nuclear receptor for thyroid hormone that shuttles rapidly between the nucleus and cytoplasm. Our prior studies showed that nuclear import of TRα1 is directed by two nuclear localization signals, one in the N-terminal A/B domain and the other in the hinge domain. Here, we showed using in vitro nuclear import assays that TRα1 nuclear localization is temperature and energy-dependent and can be reconstituted by the addition of cytosol. In HeLa cells expressing green fluorescent protein (GFP)-tagged TRα1, knockdown of importin 7, importin β1 and importin α1 by RNA interference, or treatment with an importin β1-specific inhibitor, significantly reduced nuclear localization of TRα1, while knockdown of other importins had no effect. Coimmunoprecipitation assays confirmed that TRα1 interacts with importin 7, as well as importin β1 and the adapter importin α1, suggesting that TRα1 trafficking into the nucleus is mediated by two distinct pathways. Highlights: The thyroid hormone receptor (TR) undergoes nucleocytoplasmic shuttling. We examine which importins are involved in TR nuclear import. In vitro nuclear import assays, RNAi, and GFP-trap coimmunoprecipitation assays were performed in cells. We report that importin 7, importin β1, and importin α1 mediate TR nuclear import.